Carbohydrate ingestion does not influence the change in energy cost during a 2-h run in well-trained triathletes - Brisswalter, J.; Hausswirth , C.; Vercruyssen, F.; Collardeau, M.; Vallier, J. M.; Lepers, R.; Goubault, C. (European Journal of Applied Physiology, 2000)
The aim of this study was to examine whether the increase in the energy cost of running (Cr), previously reported to occur at the end of a prolonged run, could be influenced by the ingestion of either an artificially sweetened placebo (Pl) or a 5.5% carbohydrate (CHO) solution. Ten well-trained triathletes completed three testing sessions within a 3-week period. The aim of the first session was to determine maximal oxygen uptake (V£O2max) and the velocity associated with ventilatory threshold (9VT). The second and the third sessions were composed of two submaximal treadmill runs (20 min long, 0% grade, performed at 9VT), before and after an 80-min overground run, also conducted at 9VT. During these submaximal tests, the subjects ingested (in a random order) either a Pl or CHO solution prior to the first submaximal run and every 20 min after that. During the first session, ventilatory threshold (VT) occurred at [mean (SD)] 81.2 (2.5)% V£O2max and 16.5 (0.6) km · hm1. A significant effect of exercise duration was found on Cr ((Cr) at the end of the run, whatever the solution ingested ((Cr = 5.7% and 7.01% for CHO and Pl, respectively). A reduction in the respiratory exchange ratio (from 0.98 to 0.90) was observed only at the end of the Pl trial. In this study, Cr seems to be affected only to a minor extent by substrate turnover. Moreover, the increase in the demand for oxygen, estimated from the increase in ventilation, accounted for only a minor proportion of the increase in Cr (11% and 17% for CHO and Pl, respectively). No correlation was found between the changes in Cr and the changes in the other physiological parameters recorded. These results suggest, indirectly, that Cr increases during a 2-h run at 80% V£O2max in well-trained subjects can be explained mainly by alterations in neuromuscular performance, which lead to a decrease in muscle efficiency.